2017
DOI: 10.1212/wnl.0000000000004568
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine as symptomatic treatment for Parkinson disease (Café-PD)

Abstract: This study provides Class I evidence that for patients with PD, caffeine does not significantly improve motor manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 28 publications
2
90
1
3
Order By: Relevance
“…Previous studies have shown the relationships between altered purine metabolism and PD pathology. A panel of metabolites, that is, adenosine, inosine, guanosine, hypoxanthine, and uric acid, has been reported to be altered in PD brains compared to controls (Tufi et al ; Garcia‐Esparcia et al ; Burnstock ; Postuma et al ). Our results indicated that neuroinflammation induced a significant decrement in adenosine and high levels of catabolic intermediates such as inosine, hypoxanthine, and xanthine.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the relationships between altered purine metabolism and PD pathology. A panel of metabolites, that is, adenosine, inosine, guanosine, hypoxanthine, and uric acid, has been reported to be altered in PD brains compared to controls (Tufi et al ; Garcia‐Esparcia et al ; Burnstock ; Postuma et al ). Our results indicated that neuroinflammation induced a significant decrement in adenosine and high levels of catabolic intermediates such as inosine, hypoxanthine, and xanthine.…”
Section: Discussionmentioning
confidence: 99%
“…This result was largely unexpected because the observational study associations between caffeine-containing drinks (both coffee and tea) have almost always suggested a negative association between caffeine and PD 4,24 . This has meant that caffeine has been explored as a potentially therapeutic option for PD 25 . It is not clear what would account for observing consistently negative observational associations between caffeine and PD, and a potentially detrimental effects of caffeine on PD in MR analyses, but the effect for coffee drinking in this analysis was also not in favour of a true protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…Other available therapies that might be “repurposed” for disease modification based on either epidemiological or basic science studies include caffeine and antidepressants including tricyclics, fluoxetine, and trazodone. The latter has the novel effect of potentially supressing the overactive unfolded protein response by inhibition of Phospho‐Eukaryotic Initiation Factor 2a (eIF2α‐P) activity .…”
Section: Targets For Disease Modificationmentioning
confidence: 99%